2020
DOI: 10.1016/j.psj.2020.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of digestible amino acids to energy ratios on performance and yield of two broiler lines housed in different grow-out environmental temperatures

Abstract: Two broiler lines, Line A and Line B, were fed experimental diets from 22 to 42 d with objectives to determine effects of digestible amino acids ( AA ) to metabolizable energy ratios on feed intake ( FI ), performance, and processing yield. Experimental diets were formulated to 3,150 kcal/kg with 5 levels of digestible lysine ( dLys )—80, 90, 100, 110, and 120% of recommended AA level giving g dLys/Mcal values of 2.53, 2.85, 3.17, 3.48, and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
0
10
1
Order By: Relevance
“…Moreover, Alhotan et al (2021) fed an AA density ranging from 80% to 110% of breeder recommendations to broilers exposed to cyclic HS. In contrast with the results reported by Maharjan et al (2020) , no interactions between environmental temperature and dietary AA density were observed on performance and processing data. However, linear effects of AA density indicated that BWG, feed efficiency, and breast muscle yield responded to increased AA density in both environments.…”
Section: Supplementation Of Amino Acidscontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, Alhotan et al (2021) fed an AA density ranging from 80% to 110% of breeder recommendations to broilers exposed to cyclic HS. In contrast with the results reported by Maharjan et al (2020) , no interactions between environmental temperature and dietary AA density were observed on performance and processing data. However, linear effects of AA density indicated that BWG, feed efficiency, and breast muscle yield responded to increased AA density in both environments.…”
Section: Supplementation Of Amino Acidscontrasting
confidence: 99%
“…Altering dietary density of essential AA has been shown to have promising results in heat-stressed broilers. In broilers under hot temperatures, Maharjan et al (2020) fed five levels of digestible Lys (dLys) from 80% to 120% of the recommended level with all other AA:dLys ratios held constant and observed quadratic responses in average daily gain and FCR up to the 120% dLys level, and no influence on FI. In contrast, the optimal average daily gain and FCR were closer to the 100% recommendation of dLys under thermoneutral conditions.…”
Section: Supplementation Of Amino Acidsmentioning
confidence: 99%
“…Finding the appropriate protein to energy ratio in the diet can be crucial for the optimal performance of broilers. The performance and processing yield benefits by increasing dietary amino acid density is becoming more evident ( Temim et al., 1999 ; Viera and Angel, 2012 ; Maharjan et al., 2020c ), whereas less is known regarding dietary energy density. The present study evaluated the effects of dietary ME levels ranged from 2,800 to 3,300 kcal/kg on performance parameters and processing yield characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…It also increases the need for nutrients and amino acids such as methionine, lysine and Threonine. So The growth rates of broiler under heat stress conditions depend on a sufficient supply of amino acids to produce proteins involved in various physiological functions, such as signal transduction, hormone signaling, cell structure, and antioxidant systems (Maharjan, 2020). Therefore, nutritional and management therapies can be introduced to minimize the heat stress due to high environmental temperatures in broiler production.…”
Section: Introductionmentioning
confidence: 99%